Continuous time and volume batch formulation for the multiproduct pipeline network scheduling problem. Issue 10 (2022) - Bamoumen, Meryem; Elfirdoussi, Selwa; Ren, Libo; Tchernev, Nikolay
Abstract: The pipeline is one of the most reliable and economical modes of transport. It is mainly used for petroleum products transportation over long distance. In this paper, we are interested in the multiproduct pipeline network scheduling problem in the context of mining industry. The considered pipeline network is part of OCP's pipeline network for the transportation of phosphate products. A MILP model based on continuous time and volume batch formulation is proposed. It aims to schedule a set of batches to be transported from the main pipeline to intermediate storage groups before delivered to Clients using secondary pipelines. Each batch can be composed of several blocks. The objective is to maximize the main pipeline utilization rate with smallest number of blocks to satisfy all clients' demands. A set of short-term plan horizon instances are generated and the results show that the proposed model gives effectively optimal or near-optimal solutions of these instances.